Linear Programming: Tool for Agricultural Development (LACCEI, 2024)
The current investigation proposed to design a crop rotation plan based on organic farms that improves farm income through linear programming. To carry out the investigation, the problem was defined in the farms in Mata de Plátano, El Paraiso, Honduras where they lack agricultural training and knowledge the operations on their farms do not provide competent utility or productivity and affects their income. To accomplish the objective surveys were made to know about the resources that the farms in Mata de Plátano already had. Also, a documentary review was prepared to define all the principles of crop rotation that the mathematical model must follow. Subsequently, the mathematical model was developed through Solver Excel and finally its operation was validated by comparing the results with farm's current practices. In conclusion, the investigation was carried out successfully. The mathematical model followed all the principles of crop rotation, the constraints from the current available resources, found the optimal solution to increase farms production and it was validated that the model generates more profits than the current method.